Strategi Lazada dalam Meningkatkan Retensi Pelanggan Melalui Program Loyalitas - Anggit Dyah Kusumastuti; Bima Rizki Saputra; Clarisa Elen Setiawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The tight competition in the e-commerce industry requires platforms like Lazada to implement effective strategies to increase customer retention. One of the main strategies used is a loyalty program, which includes a customer tier system, reward points, cashback, gamification, and premium membership. In addition, the role of Electronic Word of Mouth (E-WoM) also contributes to building customer trust through reviews, referral programs, and social media promotions. Customer satisfaction factors, such as service quality, delivery speed, ease of using the loyalty program, and transaction security, are important elements in the success of this strategy. This study aims to analyze the effectiveness of Lazada's loyalty program in increasing customer retention. The results of the study show that the combination of loyalty strategies and customer satisfaction significantly influences customers' decisions to continue using the Lazada platform.